Claims on Hayti. Message from the President of the United States communicating information in regard to claims of citizens of the United States on HaytiTT - - États-Unis. House of representatives. Committee on foreign affairs (1842)
United States Congress, House of Representatives, Executive ; 27th Congress, 3d Session ; doc. no. 36